2020
DOI: 10.1186/s12943-020-1140-x
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs Orchestrate Pathophysiology of Breast Cancer Brain Metastasis: Advances in Therapy

Abstract: Brain metastasis (BM) predominantly occurs in triple-negative (TN) and epidermal growth factor 2 (HER2)-positive breast cancer (BC) patients, and currently, there is an unmet need for the treatment of these patients. BM is a complex process that is regulated by the formation of a metastatic niche. A better understanding of the brain metastatic processes and the crosstalk between cancer cells and brain microenvironment is essential for designing a novel therapeutic approach. In this context, the aberrant expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 174 publications
(244 reference statements)
3
50
0
Order By: Relevance
“…miRNAs function through 6-7 base complementary binding to target mRNA and inhibition of target gene expression at the level of protein [22][23][24]. From the literature, miRNAs can work as oncogenes to promote the formation and biological changes of TME [25][26][27][28]. For example, miR-9 and miR-200s induce normal fibroblasts (NFs) in TME to transform into CAFs and promote tumor metastasis [29,30], miR-526b and miR-655 promote angiogenesis and lymphangiogenesis in TME [31], and miR-340-5p and miR-561 induce formation of immunosuppressive microenvironment [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs function through 6-7 base complementary binding to target mRNA and inhibition of target gene expression at the level of protein [22][23][24]. From the literature, miRNAs can work as oncogenes to promote the formation and biological changes of TME [25][26][27][28]. For example, miR-9 and miR-200s induce normal fibroblasts (NFs) in TME to transform into CAFs and promote tumor metastasis [29,30], miR-526b and miR-655 promote angiogenesis and lymphangiogenesis in TME [31], and miR-340-5p and miR-561 induce formation of immunosuppressive microenvironment [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The BBB is selectively permeable under normal physiological conditions. However, the pathological cues, including brain metastasis, render the loss of BBB integrity, which transforms the intact BBB into the blood–tumor barrier (BTB) and alters the permeability for therapeutic agents [ 32 , 33 , 34 ]. As the SKBrM3 cell line expresses high c-MET and ERBB1 receptors, and the combination treatment of NER and CBZ predominantly downregulated the pERK pathway in this cell line, we examined the effect of treatment on the migration of SKBrM3 cell line in vitro that mimics the human BBB to some extent ( Figure 2 E).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, miRNAs are regarded as attractive therapeutic targets for the treatment of cancer metastasis. 94 Debeb et al showed that the overexpression of miR-141 in TNBC cells enhanced BM colonization, while its knockdown inhibited the ability of inflammatory TNBC to metastasize to the brain. Additionally, high miR-141 serum levels have been associated with shorter BM-free survival ( P =0.04) and were independent predictors of PFS and OS.…”
Section: Potential Therapeutic Targets For Tnbcbm Treatmentmentioning
confidence: 99%